Dust diffusion in large-scale urban construction combining WRF and CALPUFF model—take Xiamen as an example - Zhou, Hong; Gao, Binwei; Deng, Fangdi (Journal of Environmental Engineering and Landscape Management, 2023)
With the increasing number of construction sites in cities, construction dust, as one of the essential factors affecting the atmospheric environment, urgently needs more attention. Most existing studies have studied construction dust and other particle sources comprehensively. There remains a need for research on large-scale diffusion ultimately aiming at construction dust, especially studies on the diffusion law of dust generated only by construction dust at a large-scale city level where all construction sites within the city working at the same time. To systematically explore the diffusion distribution of construction dust in such a situation, this paper takes Xiamen as the research object and puts forward a large-scale construction dust diffusion research method by integrating emission factors and combining WRF and CALPUFF model. The spatial distribution of PM10 emission during the simultaneous construction of all sites in Xiamen in 2019 was simulated. The diffusion law of dust in large-scale construction in Xiamen is obtained. On this basis, the regional contribution of construction dust PM10 in various districts of Xiamen and the best start month of each district are obtained, which provides valuable suggestions for government construction control. This research method can be effectively applied to cities similar to Xiamen.